Alpha-thalassaemia in association with beta-thalassaemia patients in Malaysia: a study on the co-inheritance of both disorders - Wee, Y.C.; Tan, K.L.; Kuldip, K.; Tai, K.S.; George, E.; Tan, P.C.; Chia, P.; Subramaniam, R.; Yap, S.F.; Tan, J. (2008)
Background/Aims: Individuals with double heterozygosity for alpha- and beta-thalassaemia and heterozygous beta-thalassaemia show a similar haematological picture. Co-inheritance of (alpha- and beta-thalassaemia in both partners may result in pregnancies with either Hb Bart's hydrops foetalis or beta-thalassaemia major, or pregnancies with both disorders. Methods: The co-inheritance of a-thalassaemia in 322 P-thalassaemia carriers in Malaysia was studied. Results: The frequency of (alpha-thalassaemia in the beta-thalassaemia carriers was 12.7 (41/322), with a carrier frequency of 7.8 for the SEA deletion, 3.7 for the -alpha(3.7) deletion, 0.9 for Hb Constant Spring and 0.3 for the -alpha(4.2) deletion. Conclusion: Double heterozygosity for (alpha- and beta-thalassaemia was confirmed in 5 out of the 41 couples and the risk of the fatal condition Hb Bart's hydrops foetalis was confirmed in two of these couples. Detection of the Southeast Asian (SEA) deletion in the Malaysian Malays in this study confirms that Hb Bart's hydrops foetalis can occur in this ethnic group. Results of this study have provided new information on the frequency and different types of alpha-thalassaemia (--(SEA), -alpha(3.7) and -alpha(4-1) deletions, Hb Constant Spring) in Malaysian beta-thalassaemia carriers.Copyright (C) 2008 S. Karger AG, Basel.